Influence of socioeconomic factors on accidental injuries in children - Shankar, Poornima; G. S., Krithika; ., Afroza; E., Balaji (International Journal of Contemporary Pediatrics, 2021)
Background: The World Health Organization (WHO) report of 2006 stated that injuries account for a significant percentage of deaths in children. Of the 2.6 million child deaths recorded, among 1-14 year old children, 15.4% are said to be due to unintentional injuries. This study aims to establish if the socioeconomic status forms a risk factor for unintentional injuries. Methods: This is a retrospective study conducted at Kempegowda Institute of Medical Sciences, Bangalore. Children between 0-18 years of age were included and case files of children admitted for unintentional injuries were studied and the socioeconomic status was analyzed. Results: This study has helped us conclude that accidental injuries although variedly distributed between families of different socioeconomic class, were not significantly associated with lower socioeconomic status, overcrowding or parental age and employment. The only factor that emerged a risk was male gender (53.66%). Conclusions: While majority of studies indicate that lower socio-economic status is associated with higher injury risk, our study did not indicate the same. Therefore, it calls for more studies which explore the various other factors.